Refluxed Synthesis of SBA-15 Using Sodium Silicate Extracted from Oil Palm Ash for Dry Reforming of Methane - Hazirah A., Razak; Nornasuha, Abdullah; Setiabudi, H. D.; Chin, S. Y.; Nurul Aini, Razali (Elsevier Ltd, 2019)
The effects of Nickel (Ni) loading on Mesoporous Silica Barbara Amorphous (SBA-15) properties and catalytic activity with respect to dry reforming of methane were studied. The mesostucture characteristics of SBA-15 synthesized from oil palm ash (OPA) waste was proven by XRD low angle and N2 adsorption-desorption isotherms. Ni/SBA-15 was prepared by the sol gel method that favours metal dispersion on the SBA-15 support. The properties of the catalysts were evaluated by XRD, BET, TEM, and FTIR. The catalytic activity of catalyst was investigated in a stainless steel fixed-bed reactor at 800°C with a 1:1 ratio of CO2:CH4 feed composition. Ni supported on SBA-15 (OPA) exhibited higher CO2 and CH4 conversion with 61.07 % and 54.65 %, respectively compared to the Ni/SBA-15 (s.s) produced using commercial sodium silicate. This result demonstrated that smaller particle size of NiO with high dispersion on the SBA-15 surface, leads to higher syngas formation compared to Ni/SBA-15 (s.s). Furthermore, the appropriate interaction and synergistic effects of Ni-SBA-15, and greater NiO surface active sites were responsible for good activity in terms of CO2 and CH4 decomposition.